2015
DOI: 10.1139/cjpp-2014-0362
|View full text |Cite
|
Sign up to set email alerts
|

Oxymatrine inhibits lipopolysaccharide-induced inflammation by down-regulating Toll-like receptor 4/nuclear factor-kappa B in macrophages

Abstract: Oxymatrine (OMT) is the quinolizidine alkaloid extracted from the Chinese herb Sophora flavescens Ait. that has many pharmacological effects and is used for the treatment of some inflammatory diseases. In this study, RAW264.7 cells and THP-1 differentiated macrophages were pretreated with various concentrations of OMT at 2 h prior to treatment with lipopolysaccharide (LPS) (1.0 μg/mL) for different durations. We detected the anti-inflammatory effect of OMT in LPS-stimulated macrophages and investigated the mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 34 publications
2
22
0
Order By: Relevance
“…Nuclear factor‐κB (NF‐κB) is an essential transcription factor involved in the pathogenesis of psoriasis. Oxymatrine has been shown to increase the phosphorylation of the inhibitor of κB‐α in the cytosol, prevent the nuclear translocation of NF‐κB, or reduce the expression level of NF‐kB p65, resulting in the inhibition of NF‐κB activation . Therefore, oxymatrine may ameliorate psoriasis via the inhibition of NF‐kB activation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nuclear factor‐κB (NF‐κB) is an essential transcription factor involved in the pathogenesis of psoriasis. Oxymatrine has been shown to increase the phosphorylation of the inhibitor of κB‐α in the cytosol, prevent the nuclear translocation of NF‐κB, or reduce the expression level of NF‐kB p65, resulting in the inhibition of NF‐κB activation . Therefore, oxymatrine may ameliorate psoriasis via the inhibition of NF‐kB activation.…”
Section: Discussionmentioning
confidence: 99%
“…Oxymatrine has been shown to increase the phosphorylation of the inhibitor of jB-a in the cytosol, prevent the nuclear translocation of NF-jB, or reduce the expression level of NF-kB p65, resulting in the inhibition of NF-jB activation. [43][44][45] Therefore, oxymatrine may ameliorate psoriasis via the inhibition of NF-kB activation. However, further studies using skin cells or related immune cells involved in the inflammatory process of psoriasis are needed to verify the underlying mechanism(s) of the effects of oxymatrine.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that OM could inhibit molecules in the TLR4 signaling pathway, decrease the levels of pro‐inflammatory cytokines, and prevent systemic inflammatory response syndrome. Zhang et al showed that the increased levels of TLR4, NF‐κB p65, IκBα, and other LPS‐induced signaling molecules in LPS‐treated macrophages were obviously suppressed by the administration of OM, which exerted antiinflammatory effects by decreasing the production of pro‐inflammatory factors and cytokines in a dose‐dependent manner (Zhang et al, ). Dong et al found that the LPS‐induced phosphorylation of ERK1/2, p38 mitogen‐activated protein kinase, and JNK in BV2 microglia cells was significantly attenuated by OM treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The direct administration of mice or immune cells with proinflammatory stimuli has been shown to promote the production of reactive oxygen species via nitrite [24,25]. The increased nitrite together with reactive oxygen species causes oxido-nitrosative stress and neurotoxic effects [26].…”
Section: Discussionmentioning
confidence: 99%